Unveiling the Impact of Psychological Traits on Innovative Financial Decision-making in Small Tourism Businesses - Navjot Sandhu (14152026) (2022)
Understanding factors affecting innovative financial decision-making involves the usage of more than one theory-driven model including those related to psychological behaviour (e.g. theory of planned behaviour). This study validates a conceptual framework extending the traditional financing model (TFM) and behavioural financial decision (BFD) to explain innovative financial decision-making utilising both qualitative and quantitative approaches. Based on a sample of 140 small tourism businesses, employing structured equation modelling, the findings reinforce the importance of the behavioural approach on innovative financial decision-making in small tourism businesses. The findings does not only make a respectable contribution the field, but also offer a practical evidence for the adaptation of the theory of planned behaviour in developing countries. Other Information Published in: Journal of the Knowledge Economy License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s13132-022-00987-y